Site-Level Variability in 30-Day Patient Outcomes After Transcatheter Mitral Valve Repair in the United States. Issue 12 (December 2020) - Malik, Ali O.; Chhatriwalla, Adnan K.; Saxon, John; Hejjaji, Vittal; Stebbins, Amanda; Jones, Philip G.; Cohen, David J.; Arnold, Suzanne V.; Vemulapalli, Sreekanth; Wegermann, Zachary K.; Kosinski, Andrzej; Spertus, John A.
Abstract : Background: Clinical trials have demonstrated health status benefit of transcatheter mitral valve repair (TMVr) with MitraClip in patients with mitral valve regurgitation. Real-world site-level variability in health status outcomes for TMVr, and factors associated with this variability, are unknown. Methods: All patients undergoing TMVr procedure with MitraClip between November 2013 and March 2019 in the Transcatheter Valve Therapy Registry were included. Health status was measured at baseline and 30 days with the Kansas City Cardiomyopathy Questionnaire (KCCQ) Overall Summary (OS) score. Site-level variability in 30-day change in KCCQ-OS was examined by calculating the median odds ratio from a hierarchical logistic regression model, with ≥20-point improvement as the dependent variable. To define the extent to which patient characteristics, procedural characteristics (residual mitral valve regurgitation, periprocedural bleeding), site volume, and patients' baseline health status accounted for variability in outcomes, the proportion of variability ( R 2 ) explained by sequentially adding these variables to the model was quantified. Results: Across 339 sites, 12 415 patients (mean age 79.0±9.5 years, 46.1%. females, 89.5% White) completed baseline and 30-day health status assessments. Mean KCCQ-OS score was 43.0±24.4 at baseline and 67.0±24.9 at 30-day follow-up. Across sites, the proportion of patients achieving a ≥20-point improvement in KCCQ-OS ranged from 12.5% to 100% and the adjusted median odds ratio was 1.58 (95% CI, 1.46–1.69). The greatest contribution to the variability in health status outcomes was from patients' baseline KCCQ-OS score ( R 2 =25%) with <1% of the variability explained by patient and procedural characteristics, and annual site volume. Conclusions: There is moderate variation across sites in their patients' achievement of health status benefits from TMVr, with patient's baseline health status accounting for the largest proportion of this variation. This underscores the importance of patient selection in supporting more consistent health status benefit from TMVr. Abstract : Supplemental Digital Content is available in the text.